2015
DOI: 10.3238/arztebl.2015.0311
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Simple Elbow Dislocation in Adults

Abstract: SUMMARYBackground: Simple elbow dislocation is a complex soft-tissue injury that can cause permanent symptoms. Its incidence is 5 to 6 cases per 100 000 persons per year. Its proper treatment is debated; options range from immobilization in a cast to surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 40 publications
1
43
0
5
Order By: Relevance
“…Recently, Hackl et al published a comprehensive review regarding the treatment of simple elbow dislocations. The authors concluded that there is still lack of evidence for the individual treatment decision of simple elbow dislocations [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hackl et al published a comprehensive review regarding the treatment of simple elbow dislocations. The authors concluded that there is still lack of evidence for the individual treatment decision of simple elbow dislocations [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A closed dislocation with or without a neurovascular impairment should be followed by immediate closed reduction of the elbow joint in the emergency room (1). If there are any signs of brachial artery injury (absent or weak pulsations of ulnar and radial arteries, excessive swelling at the elbow joint, median nerve palsy), arteriography is the first choice test as Doppler sonography is more user-dependent and might be difficult to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A dislocation of the elbow joint is the second most common dislocation after the shoulder joint with the incidence of 5-6 cases per 100,000 a year, of which about 90% are posterior or posterolateral dislocations (1)(2)(3). The most common mechanism of the injury is the fall on the hand with an outstretched elbow which creates hyperextension forces in the joint (4).…”
Section: Introductionmentioning
confidence: 99%
“…So wie die einfache Ellenbogenluxation unterschiedlich schwere Instabilitätsausmaße annehmen kann, so reicht die Therapie von der einfachen Ruhigstellung des Gelenks für wenige Tage bis zum komplexen operativen Eingriff. Bislang herrscht in der Fachliteratur keine Einigkeit über die bestmögliche Therapie der Ellenbogenluxation mit ihren unterschiedlich ausgeprägten Instabilitäten [14]. Neben den beschriebenen Indikationen sollten Alter, berufliche und sportliche Anforderungen sowie der Wunsch des Patienten individuell bedacht werden.…”
Section: Säulenmodell Von Ring Und Jupiterunclassified